Assessing the adoption of improved bean varieties in Rwanda and the role of varietal attributes in adoption decisions - LaRochelle, Catherine; Asare-Marfo, Dorene; Birol, Ekin; Alwang, Jeffrey (International Food Policy Research Institute, 2016)
Beans are grown by nearly all rural households in Rwanda, provide a large share of calorie intakes, and are a vital source of proteins and micronutrients. Because of the importance of this crop, significant research efforts have been devoted to select, breed, and disseminate bean varieties with superior production, consumption, and market attributes, while addressing challenges related to climate changes and food insecurity. As a result, nearly 100 bean varieties have been released in Rwanda over the last four decades. This study aims at documenting this effort; it assesses adoption of improved bush and climbing bean varieties, identifies determinants of and barriers to adoption, and analyzes farmers' preferred variety attributes. Based on recent household data, 86 and 50 percent of households have adopted improved climbing and bush bean varieties, respectively. Adoption is positively associated with membership in farmers associations and size of landholding devoted to bean cultivation. Agro-climatic factors are strong predictors of adoption in general and of specific popular improved varieties. Varietal attributes most associated with high adoption rates are high yield, early maturity, storability, and taste. Findings from this study can serve to inform future breeding and dissemination efforts of improved bean varieties in Rwanda.